Santri in the Frame of Religious Harmony - Aksa, Ahmad Habiburrohman; Hakim, Muh. Luthfi (The Institute of Research and Service Community IPMAFA Pati, 2023)
In Indonesia's harmony context, the role of santri and pesantren is related to maintaining religious harmony. Pesantren is one form of religious education that has become a significant focus in Indonesia, especially after the emergence of several radical acts in the name of religion. This article will dig deeper into the role of Santri in maintaining religious harmony in Indonesia. We will explore how education in pesantren provides a strong foundation for the values of harmony, how Santri engages in interfaith activities, and how their contributions help maintain peace in the country. The results of this research show that first, in the context of religious harmony in Indonesia, santri in pesantren has a significant role in maintaining and strengthening inter-religious harmony. Second, they have a central role in internalizing the values of harmony, tolerance, and anti-radicalism.